Violência, clima e expectativas escolares: evidências das escolas estaduais da Região Metropolitana de Belo Horizonte - Luiza Meira Bastos (2016)
The aim of this work is to understand the relation between violence and school organization, and how these factors influence the expectation about students schooling. The analysis is divided in two stages: the first one seeks to understand how factors of collective efficacy influence the occurrence of infractions within schools. The second one works with the concept of schooling expectations and includes violence in the concept of school environment, which is present in the theory of school effectiveness, in order to understand how school organization affects the expectation about students' schooling. To this end, INEP - Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira - data were used about schools of Minas Gerais as well as data from a sample survey of CRISP - Centro de Estudos em Criminalidade e Segurança Pública - about school violence in Belo Horizontes metropolitan area. Econometric analysis results suggest that school organizational ability affects the occurrence of violence committed by students. The perceived school environment is negatively impacted by students being victims of assault or theft within school or the identification of the existence of gangs. The improvement in school environment has, in turn,a positive effect on expectations about high schooling rates among adolescents. Events of violence have an indirect effect via school schooling - on the expectations of high schooling rates. It can thus be inferred that working with collective efficacy for school organizationalunderstanding not only directly affects events of violence, but it also indirectly helps students as far as educational perspective is concerned.